Geac System21 commerce.connect implementation on the IBM eserver iSeries server - Johng, Yessong (IBM, International Technical Support Organization, 2002)
This IBM Redbooks publication introduces the new Geac commerce platform .connect applications -- the call.connect and vendor.connect applications. These applications extend and enhance the capabilities of Geac System21 into the intranet and Internet. This book targets consultants or customers who work with these .connect applications. It explains how to install, maintain, integrate, and manage these applications on the IBM eServer iSeries server. It also helps you to understand the architecture and middleware used by the applications. Prior to reading this book, you must be familiar with the basic, traditional use of the iSeries or AS/400 and System21. For example, you should know how to enter simple commands and understand such concepts as the library list. Similarly for System21, you should be familiar with the menus and such tasks as defining a System21 user. As necessary throughout the book, detail is provided about the newer, less traditional features of the iSeries such as the integrated files system (IFS), Qshell, Java, and WebSphere.
"December 2002.". - "SG24-6526-00.". - Includes bibliographical references and index. - Print version record
Keywords: Geac System 21; Business enterprises -- Data processing; Electronic commerce; Call centers -- Computer network resources; Entreprises; Informatique; Commerce électronique; Business enterprises; Data processing; Call centers; Computer network resources